New agents to reduce cholesterol levels: implications for nephrologists - Del Vecchio, Lucia; Baragetti, Ivano; Locatelli, Francesco (Nephrology, dialysis, transplantation, 2020)
Abstract Statins and ezetimibe effectively reduce the burden of cardiovascular (CV) disease in patients with chronic kidney disease (CKD). Unfortunately, many subjects still die or have CV events despite cholesterol-lowering therapy. This is particularly true in patients with more advanced CKD. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease that induces the degradation of the low-density lipoprotein receptor by targeting it for lysosomal destruction. Its inhibition causes a dramatic fall in cholesterol levels on top of maximized statin therapy. This goal is obtained with different therapeutic approaches, spanning from monoclonal antibodies to non sense oligonucleotides and silencing RNA (siRNA). Two human, monoclonal antibodies are approved for clinical use; they are still very expensive. Both agents significantly lower cholesterol levels. Evolocumab and alirocumab reduce significantly the risk for CV disease without relevant safety issues. Inclisiran is an siRNA molecule that produces PCSK9-specific RNA silencing. Data from a Phase II study showed significant cholesterol-lowering efficacy. The experience accumulated so far is limited in the CKD population. PCSK9 inhibition also has the potential to reduce the burden of CV in this subset by obtaining a much greater decrease in serum cholesterol compared with statin therapy or ezetimibe. Doubts exist that this approach will improve the outcome of dialysis patients, in whom vascular calcifications predominate.